Inducible Mis- and Over-Expression of PKCIW Regulates the Expression of AMH and P450arom in Chicken Embryo Fibroblast - Gong, P.; Gong, Y.Z.; Yang, Y.P.; Yang, Y.; Feng, Y.P.; Li, S.J.; Peng, X.L. (International Journal of Poultry Science, 2009)
Sex in birds is determined genetically as in mammals and a Z-linked gene DMRT1 is required for testis development. But it remains possible that the W chromosome contains a similarly critical factor for female development. The W-linked gene PKCIW was put forward as the seductive candidate for avian sex determination and/or sex differentiation. Mis-expression and over-expression of PKCIW were performed respectively in male and female chicken embryo fibroblast with tet-on inducible expression system in this study. The results of RT-PCR showed that with the PKCIW recombinant vector introducing, PKCIW mRNA expression was significantly improved in female chicken embryo fibroblast and was close to that of the female controls and in male chicken embryo fibroblast, in which normally there was no expression. Both mis- and over-expression of PKCIW led to up-regulated expression of P450arom and down-regulated expression of AMH, while large increase of P450arom in female and large decrease of AMH in male appeared. With mis- and over-expression of PKCIW, there was no significant change of FOXL2, SOX9, DMRT1 and ATP5A1W mRNA expression. These results showed the possible regulatory effect of PKCIW on AMH and P450arom in transcription level.